Gentrificação por contágio no Bairro Intendente - Roussado, Bruna Patrícia Gomes (2019)
The process of gentrification, a concept named by Ruth Glass when describing the Islington Neighborhood nobility in 1964, has expanded in the way and importance it has touched cities, gaining particular relevance in Architectural Studies. This master thesis proposes an analysis of Bairro do Intendente in the light of this concept, trying to understand how, as an architectural procedure, the gentrification process is transmitted and concretized in a contagious form. To make it operational, we limited the analyses to Largo do Intendente, thinking of it as a device2.In the case under study, gentrification comes to the Intendente from the axis of Terreiro do Paço - Rua Augusta, flowing to Almirante Reis with the rehabilitation of Martim Moniz. Thus, and by contagion, it transformed the Intendente. We propose, therefore, to think through the field observations, the Intendente public space as an open public space also characterized by streets, squares and an art installation. Regarding the methodological questions of device analysis, Largo do Intendente, we follow two axes: one more theoretical, exploring the concepts Actor Network Theory (ANT), which allowed the centrality of the notion of Backstage to be reached; another more practical, anchored to anthropological precepts, such as direct observation, and which proved useful in the illustration of the place, complemented by interviews with the actors that make up the human geography of this place. From the intersection between theoretical reflection and field notes, it became possible to prove the dynamics established between the disqualified city and the new gentrified urban landscape.